Structural breaks and explosive behavior in the long-run: The case of Australian real house prices, 1870-2020 - Vicente Esteve García; María A. Prats (Economics: The Open-Access, Open-Assessment Journal, 2021)
In this article, we use tests of explosive behavior in real house prices with annual data for the case of Australia for the period 1870-2020. The main contribution of this paper is the use of very long time series. It is important to use longer span data because it offers more powerful econometric results. To detect episodes of potential explosive behavior in house prices over this long period, we use the recursive unit root tests for explosiveness proposed by Phillips et al. (2011), (2015a,b). According to the results, there is a clear speculative bubble behavior in real house prices between 1997 and 2020, speculative process that has not yet been adjusted.
Keywords: E31; R21; E62; H62; R39; 330; explosiveness; house price; multiple structural breaks; recursive unit root test